Histórias de doação de rim: explorando narrativas e repertórios interpretativos de doadores - Fernandes, Luciana Freitas (2011)
Living organ donation has been considered an alternative to the shortage of organs for transplantation; as such it is part of medical procedures where we can see the intricate relationship between biotechnology and the process of meaning making in everyday life. This research discusses organ donation, understood as a social practice supported by a network of various human and non human actors. More specifically, our research focuses on narrative types and interpretative repertoires used by living kidney donors to build versions about organ donation. Interviews were conducted with three donors, two potential donors and three recipients at the kidney transplantation department of Hospital Universitário Walter Cantídio, in Fortaleza (CE-Brazil). The interviews were transcribed and analyzed in terms of narrative types and interpretative repertoires in use. Among the results, we can highlight the predominant use of restitution narratives to talk about kidney donation as an expedient to restore the recipient’s lost health. This finding shows the powerful discursive matrix, supported by biotechnology and contemporary Western medicine, which values health as a normal condition and establishes the need for repair in cases of illness. Among the arguments and metaphors used to build the donation, we highlight the act of love and gift of life, which compose the “language of gift”. The donor tends to be positioned as a brave, heroic person, whose altruism saves lives; while the organs to be donated are formulated as rare and valuable resources that must be recycled, specially in case of a close parent’s need. We conclude that the ways of telling stories of renal donation and the interpretive repertoires used in those narratives produce specific effects in the living transplant actors’ network, functioning to promote the recruitment of donors in the family.